The Second World War - Keegan, John 1934-2012 (Viking, 1990)
A chronological history of each theater of the war, analyzing five battles for their distinctive kind of warfare of the period.
Keywords: Geschichte; Tweede Wereldoorlog; Weltkrieg (1939-1945); World War, 1939-1945; Zweiter Weltkrieg